Bottom‐up Meets Top‐down: Complementary Physiologically Based Pharmacokinetic and Population Pharmacokinetic Modeling for Regulatory Approval of a Dosing Algorithm of Valganciclovir in Very Young Children. Issue 6 (29th September 2016) - Jorga, K; Chavanne, C; Frey, N; Lave, T; Lukacova, V; Parrott, N; Peck, R; Reigner, B
Abstract : Population pharmacokinetic (PopPK) and physiologically based pharmacokinetic (PBPK) models are frequently used to support pediatric drug development. Both methods have strengths and limitations and we used them complementarily to support the regulatory approval of a dosing algorithm for valganciclovir (VGCV) in children <4 months old. An existing pediatric PBPK model was extended to neonates and showed that potential physiological differences compared with older children are minor. The PopPK model was used to simulate ganciclovir (GCV) exposures in children with population typical combinations of body size and renal function and to assess the effectiveness of an alternative dosing algorithm suggested by the US Food and Drug Administration. PBPK and PopPK confirmed that the proposed VGCV dosing algorithm achieves similar GCV exposures in children of all ages and that the alternative dosing algorithm leads to underexposure in a substantial fraction of patients. Our approach raised the confidence in the VGCV dosing algorithm for children <4 months old and supported the regulatory approval .